SYNTHESIS OF 2-HIDROXYXANTHONE FROM XANTHONE AS A BASIC MATERIAL FOR NEW ANTIMALARIAL DRUGS - Amanatie, Amanatie; Jumina, Jumina; Mustofa, Mustofa; M, Hanafi; Kadidae, La Ode; I, Sahidin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this research is to synthesize 2-hydroxyxanthone from xanthone and to evaluate its antiplasmodial activity. Methods: The synthesis of 2-hydroxyxanthone followed the sequence of these synthetic stages, namely: 2-nitroxanthone, 2-aminoxanthone, and 2-hydroxyxanthone. The products were separated by chromatography methods including thin layer chromatography and vacuum liquid chromatography. Compound structures of the isolated products were determined based on their infrared and nuclear magnetic resonance spectra. To support these findings, the spectra were also matched to the corresponding data from literatures. The biological properties of the synthetic compound were evaluated toward Plasmodium falciparum 3D7. Results: 2-nitroxanthone was obtained as a brownish-yellow crystal in 69.00% yield with Madhya Pradesh of 181Â°C. Reduction of 2-nitroxanthone using SnCl2.2H2O/hydrogen chloride produced 2-aminoxanthone as a pale-yellow solid in 60.60% yield. Finally, the desired 2-hydroxyxanthone was achieved by initially reacting 2-aminoxanthone with sodium nitride to produce diazonium salt. Then, hydrolysis of the salt yielded 2-hydroxyxanthone as a white solid in 69.81% yield. Synthesis of 2-hydroxyxanthone from xanthone had an overall yield of38.35%. In vitro antiplasmodial assay against P. falciparum 3D7 showed that the half maximal inhibitory concentration value was 0.44 Î¼g/mL. Conclusions: An antimalarial compound (2-hydroxyxanthone) was successfully synthesized from xanthone in three steps of synthetic reactions, i.e., the formation of 2-nitroxanthone, 2-aminoxanthone, and 2-hydroxyxanthone. Â 